Experimental investigation on the application of FDM 3D printed conductive ABS-CB composite in EMI shielding. (September 2022) - Jayanth, N.; Senthil, P.; Mallikarjuna, B.
Abstract: Acrylonitrile butadiene styrene (ABS) is a petroleum-based thermoplastic primarily used in fused deposition modeling (FDM) based 3D printing and injection molding applications because of its low cost and recyclability. The addition of carbon black (CB) makes ABS conductive and can be used in electronic applications. In this experimental work, the electromagnetic interference (EMI) shielding performance of 3D printed ABS-CB composite with varying thickness (0.2–2 mm) is investigated in the frequency range of 1 GHz–12 GHz and maximum shielding effectiveness (SE) is obtained for 2 mm absorber thickness at 2.4 GHz (S-band). Also, the composite has been characterized for its electrical and mechanical properties. The electrical conductivity increases with the inclusion of CB. But, the mechanical properties such as tensile and impact strength reduced with a rise in the CB content. Highlights: FDM 3D printed ABS-CB is used as a low-cost absorber for EMI shielding applications. The EMI-SE value increases with an increase in thickness of the ABS-CB sheets. The ABS-CB sheets exhibited better EMI shielding performance in S-band and C-band. Low-cost absorbers with complex structures can be made using FDM in a short time. The material wastage in FDM is less when compared to the conventional processes.